Crystal structure of human nucleosome core particle containing enzymatically introduced CpG methylation. Issue 6 (3rd May 2016) - Fujii, Yoshifumi; Wakamori, Masatoshi; Umehara, Takashi; Yokoyama, Shigeyuki
Abstract : Cytosine methylation, predominantly of the CpG sequence in vertebrates, is one of the major epigenetic modifications crucially involved in the control of gene expression. Due to the difficulty of reconstituting site‐specifically methylated nucleosomal DNA at crystallization quality, most structural analyses of CpG methylation have been performed using chemically synthesized oligonucleotides, There has been just one recent study of nucleosome core particles (NCPs) reconstituted with nonpalindromic human satellite 2‐derived DNAs. Through the preparation of a 146‐bp palindromic α‐satellite‐based nucleosomal DNA containing four CpG dinucleotide sequences and its enzymatic methylation and restriction, we reconstituted a 'symmetric' human CpG‐methylated nucleosome core particle (NCP). We solved the crystal structures of the CpG‐methylated and unmodified NCPs at 2.6 and 3.0 Å resolution, respectively. We observed the electron densities of two methyl groups, among the eight 5‐methylcytosines introduced in the CpG‐fully methylated NCP. There were no obvious structural differences between the CpG‐methylated 'symmetric NCP' and the unmodified NCP. The preparation of a crystallization‐grade CpG‐methylated NCP provides a platform for the analysis of CpG‐methyl reader and eraser proteins. Abstract : Methylation of CpG dinucleotides is one of the major epigenetic modifications controlling gene expression. We report the reconstitution of a human nucleosome core particle (NCP) containing DNA with fully methylated CpG dinucleotides. A comparison of the crystal structures of the CpG‐methylated and unmodified NCPs revealed that the CpG methylation itself does not detectably affect the NCP structure at atomic resolution.